Recharge Oscillator Mechanisms in Two Types of ENSO - Ren, Hong-Li; Jin, Fei-Fei (Journal of climate, 2013)
The El Niño–Southern Oscillation (ENSO) tends to behave arguably as two different “types” or “flavors” in recent decades. One is the canonical cold-tongue-type ENSO with major sea surface temperature anomalies (SSTA) positioned over the eastern Pacific. The other is a warm-pool-type ENSO with SSTA centered in the central Pacific near the edge of the warm pool. In this study, the basic features and main feedback processes of these two types of ENSO are examined. It is shown that the interannual variability of upper-ocean heat content exhibits recharge–discharge processes throughout the life cycles of both the cold tongue (CT) and warm pool (WP) ENSO types. Through a heat budget analysis with focus on the interannual frequency band, the authors further demonstrate that the thermocline feedback plays a dominant role in contributing to the growth and phase transitions of both ENSO types, whereas the zonal advective feedback contributes mainly to their phase transitions. The westward shift of the SSTA center of the WP ENSO and the presence of significant surface easterly wind anomalies over the far eastern equatorial Pacific during its mature warm phase are the two main factors that lead to a reduced positive feedback for the eastern Pacific SSTA. Nevertheless, both the WP and CT ENSO can be understood to a large extent by the recharge oscillator mechanism.